The internalization of Pappaseng's value in social studies learning - Nur Ramadani, Andi; Anwar, Anwar; Ramli, Nurleli; Said, Hamdanah; Herawaty, Hasmia (JIPSINDO, 2024)
Pappaseng is a local value of the Bugis-Makassar community that contains values about life that encompass moral and ethical values that are expected to shape students' character amid the current globalization. The study aims to describe the procedure of internalization of Pappaseng values in IPS learning as an attempt to cultivate the student's character. Qualitative research methods with the type of field research are used to answer research problems. Data was collected through direct classroom observation, interviews with teachers and students, and identifying teacher learning tools. The results showed that there were several Papapseng values in the learning process, namely akkeagamang (religious) value, lempu (honest) value, warani (brave) value, siri (self-esteem) value, sipakatau (appreciate) value, and getteng (tight) value. The planting of its values in learning is inseparable from supporting and inhibiting factors. Teachers carry out the internalization of its values in social studies learning by modifying and improvising social studies teaching methods and materials that are relevant to Pappaseng spontaneously without being stated in the learning tool or lesson plan.